Inclusive education practices in rural communities: A community-based empowerment model for gender equality - Mardliyah, Sjafiatul; Widyaswari, Monica; Dewi, Putri Aisyiyah Rachma; Nugroho, Rivo; Firman, Shobri; Mardiani, Desika Putri; Suji, Suji (Edelweiss Applied Science and Technology, 2025)
This study examines the role of Tanoker Ledokombo in promoting gender equality and social inclusion in Jember through a community-based approach. Using Pierre Bourdieu’s theoretical framework, this study explores the use of social and cultural capital in creating a new habitus that supports diversity. The findings show that Tanoker successfully facilitates women’s empowerment through skills training, active participation in economic activities, and cultural festivals. This approach gives women increased financial independence and builds self-confidence and societal position. Cultural festivals become inclusive spaces that celebrate diversity, facilitate dialogue between community members, and strengthen social networks. Cultural practices such as local craft-making preserve traditions and create equal economic opportunities for all community members. This approach shows that women’s empowerment involves creating an environment that supports active participation and collaboration. Tanoker also successfully reconfigures gender norms by transforming community habitus, allowing women to challenge traditional stereotypes and strengthen their agency. By leveraging social and cultural capital, Tanoker promotes community solidarity and builds inclusive social structures. This study provides practical implications for developing community empowerment policies, highlighting the importance of cross-sector collaboration and evidence-based approaches. The Tanoker empowerment model can be adapted to other contexts to support gender equality and social inclusion. This study confirms that cultural and community-based social practices are important catalysts for sustainable social change.